Factors Affecting the Corruption Rate: Audit Opinion, Audit Findings, and Follow-up of Audit Results - Cris Kuntadi; Didi Suryadi; Galih Anggriawan (Journal of Accounting and Finance Management, 2023)
This article discusses the factors that affect the level of corruption as the dependent variable. This study is a literature review that describes the effect of the audit opinion, audit findings, and follow-up on audit results on the level of corruption, this article is a study in applied administration to increase the literacy of the influence between variables for further research purposes. The literature review results are that audit opinion, audit findings, and follow-up on audit results affect the level of corruption.